RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES TOWARDS ADHERENCE IN DETECTION OF CERVICAL CANCER - Fadhilah Sari; Pungky Mulawardhana; Lestari Sudaryanti (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Cervical cancer is an uncontrolled cell growth that occurs in the cervix caused by the Human Papilloma Virus (HPV) virus.  Early detection programs for cervical cancer can be done in several ways, including Visual Inspection of Acetic Acid (IVA), pap smear, colposcopy, cervicography, and pap net. This method has been shown to reduce the incidence of invasive cervical cancer by the amount and mortality of cervical cancer. The purpose of this study was to determine the relationship between knowledge and attitudes towards Women of Childbearing Age (WCA) compliance in early detection of cervical cancer at the Ulak Karang Health Center in Padang City. Method: Cross Sectional. The population in this study was all WCA mothers (19-69 years old) in the working area of the Ulak Karang Health Center in Padang City as many as 2,916 people with a total sample of 97 people taken using quota sampling. This research was carried out in the working area of the Ulak Karang Health Center, Padang City in May-July 2023. The variables in this study are knowledge, attitudes and compliance with IVA examination. Data were analyzed univariately, bivariately (chi square) and multivariate. Results: There was a significant association between knowledge and WCA compliance in early detection of cervical cancer (p value 0.000). There was a significant relationship between attitude and WCA compliance in early detection of cervical cancer (p value 0.000). The relationship between knowledge and attitudes towards adherence is that there is a significant relationship between knowledge and attitudes towards WCA adherence in early detection of cervical cancer (p value 0.000). Conclusion: There is a relationship of knowledge and attitudes towards WCA compliance in early detection of cervical cancer.